Structural unemployment and precarious work in a depressed labour market: Old and new trends in a southern European country - Valadas, Carla (2016)
In the wake of the 2008 economic and financial crisis, the labour market situation deteriorated in many European countries. Beyond common, apparently converging patterns, unemployment and precarious work do not have the same meaning, are not addressed the same way nor produce similar results in every society. In countries like Portugal increasing levels of unemployment and precarious work are also the result of structural problems and ill-conceived employment and educational policies, which are themselves in a process of recommodification. The aim of this paper is to analyse changes in employment and unemployment ocurring in a low and fragmented social protection system through a sociological institutionalism lens. Empirical data is provided by the analysis of statistics, documental analysis and semi-structured interviews.